Exploring households experiencing and at risk of homelessness: Linking homelessness case level data to Census 2021 - Dilly Stephenson; Jen Hampton (International Journal of Population Data Science, 2023)
This paper describes linkage of Homelessness Case Level Collection (H-CLIC) data to Census 2021, allowing researchers to better understand households experiencing and at risk of homelessness. This fits within a wider portfolio of Better Outcomes Through Linked Data (BOLD) pilot projects, developing research possibilities and partnerships within the homelessness research sphere.